Firelight - Kibuishi, Kazu, 1978- (New York, NY : Graphix, an imprint of Scholastic, 2016)
"Emily, Trellis, and Vigo visit Algos Island, where they can access and enter lost memories. They're hoping to uncover the events of Trellis's mysterious childhood -- knowledge they can use against the Elf King. What they discover is a dark secret that changes everything. Meanwhile, the Voice of Emily's Amulet is getting stronger, and threatens to overtake her completely"
Keywords: Amulets -- Comic books, strips, etc; Brothers and sisters -- Comic books, strips, etc; Supernatural -- Comic books, strips, etc; Elves -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Brothers and sisters -- Juvenile fiction; Fantasy comic books, strips, etc; Graphic novels; Comics (Graphic works)